Avaliação da qualidade nutricional e funcional do óleo da pupunha (Bactris gasipaes Kunth) - SOARES, Stephanie Dias (2023)
Atherosclerosis is a cardiovascular disease derived from excess body fat and large caliber, forming atheroma plaques, and is often hospitalized for the low consumption of foods rich in protective bioactive compounds. Thus, it is important to add relaxing food sources, especially native palm trees, which produce edible fruits with high nutritional value. However, the scarce are the studies on their properties. Objective: to evaluate the nutritional and functional profile of red bark peach palm oil (Bactris gasipaes Kunth) and its potential as hypocholesterolemic and antithrombogenic. Material and methods: the analyses followed AOAC and AOCS standards. Results: the peach palm pulp presented a mean of 2.45 mg KOH/g and a mean of 5.47 mEq/Kg. Its main bioactive compound of βcarotene presented an average of 8.324 μg/100g and the value of Retinol Activity Equivalent while provitamin A (1.390, 13 μg/100g, on average). His vector guide had a higher content of saturated fatty acids (53.74%), with emphasis on palmitic acid (50.57%); 46.25% of unsaturated fatty acids, with an average of 39.66% of monounsaturated fatty acids and 6.59% of polyunsaturated fatty acids, showing an excellent source of omega 3. Antiatherogenic, antithrombogenic and hypocholesterolemic levels were, on average, 1.10, 2.04 and 0.84), confirming a high functionality of peach palm oil and a greater amount of antiatherogenic fatty acids. These data express aspects of high relevance for an advance of the facts for direct consumption and the.